Pembelajaran Puisi Selaras Abad 21 - Dipa Nugraha (IKIP PGRI Bojonegoro, 2023)
Abstract: Poetry learning that is adaptive to the needs of students in the 21st century has not been much discussed in Indonesia. This article aims to review several important matters related to poetry learning in the 21st century. This article also discusses the concepts of “physical structure” and “inner structure” coined by Waluyo which are very dominant in poetry learning in Indonesia in the context of the potential for continuing their use in poetry learning in the 21st century at high school and college levels. This article is a literature review articlearticle by library research method through careful reading of books or articles that are relevant to the topic of this article was conducted. The literature review came to the conclusion that appreciation theory or poetry studies with the terms